Innovative Digital Tools for Enhancing Phonemic Awareness among Learners with Mild Cognitive Impairment in Calabar Education Zone of Cross River State, Nigeria (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Learners with mild cognitive impairment (MCI) often struggle with reading comprehension, especially auditory discrimination, memory retention, and linguistic processing, which hinders their ability to acquire foundational reading skills through conventional instructional approaches. This pretest-posttest quasi-experimental study investigated the effect of graphic organizers as an instruction strategy on reading comprehension among pupils with MCI in public primary schools within Calabar Education Zone, Cross River State. 80 pupils with MCI were purposively selected. Analysis of Covariance (ANCOVA) and Multiple Classification Analysis (MCA) were used to test the three hypotheses. Results indicated that graphic organizers significantly improved reading comprehension for pupils with MCI (F-ratio = 85.329, p < 0.05), while gender had no significant effect on the outcomes (F-ratio = 0.344, p > 0.05). A significant interaction effect of graphic organizers on reading comprehension improvements was also observed (F-ratio = 0.305, p < 0.05). The findings underscore the necessity of training workshops for educators on the use of graphic organizers and advocate for gender balance in grouping pupils with MCI for such interventions, highlighting the effectiveness of graphic organizers as tools for enhancing reading comprehension in pupils with MCI.